Generalized metamaterials: Definitions and taxonomy - Kim, Noori (2016)
This article reviews the development of metamaterials (MM), starting from Newton's discovery of the wave equation, and ends with a discussion of the need for a technical taxonomy (classification) of these materials, along with a better defined definition of metamaterials. It is intended to be a technical definition of metamaterials, based on a historical perspective. The evolution of MMs began with the discovery of the wave equation, traceable back to Newton's calculation of the speed of sound. The theory of sound evolved to include quasi-statics (Helmholtz) and the circuit equations of Kirchhoff's circuit laws, leading to the ultimate development of Maxwell's equations and the equation for the speed of light. Be it light, or sound, the speed of the wave-front travel defines the wavelength, and thus the quasi-static (QS) approximation. But there is much more at stake than QSs. Taxonomy requires a proper statement of the laws of physics, which includes at least the six basic network postulates: (P1) causality (non-causal/acausal), (P2) linearity (non-linear), (P3) real (complex) time response, (P4) passive (active), (P5) time-invariant (time varying), and (P6) reciprocal (non-reciprocal). These six postulates are extended to include MMs.